O miejsce przy stole… Państwo wobec nauk humanistycznych i społecznych - Brzeziński, Jerzy Marian (Człowiek i Społeczeństwo, 2020)
The article looks at the problem of inadequacy of evaluation procedures used to assess the level of research applied by government institutions (in particular Science Evaluation Committee) to research units (institutes of Polish Academy of Sciences) and university units in relation to the actual research practice of humanities and social sciences. The author concentrates on the negative consequences for these sciences resulting from the application of the promoted model –stemming from the research practice characterising science, biological science and engineering – which consists in presenting research achievements by researchers. One of such evaluation practices distorting the real understanding of research achievements in the field of humanities and social sciences is marginalising the significance of monographs. The author takes a critical view of the new law on science and higher education introduced in 2018. New solutions which the law brought have become a source of problems concerning the accuracy of the assessment of research achievements in these disciplines. The author is particularly critical of the list of publishers imposed by the Ministry of Science and Higher Education. In his opinion this list should be abandoned. He also sees flaws in the compiled list of scientific journals. Still, despite critical remarks expressed by the academic community, the ministry has not relinquished the practice of automatic conversion of scientific achievements into points. In the author’s view, an appropriate solution would be peer review – especially for humanities and social sciences (particularly for the evaluation of the scientific merit of monographs). The article contributes to the discussion on the future shape of evaluation procedure of the quality of research activity which is being prepared by the Ministry of Science and Higher Education and which will come into effect in 2022.